BS10 A carvedilol analogue, VKII-86, prevents hypokalaemia-induced ventricular arrhythmia through novel multi-channel effects. (4th June 2021) - Robinson, Victoria; Alsalahat, Izzeddin; Freeman, Sally; Antzelevitch, Charles; Barajas-Martinez, Hector; Venetucci, Luigi
Abstract : Background and Purpose: Hypokalaemia is the most common electrolyte disturbance with a significant mortality due to the occurrence of ventricular arrhythmia. There is currently no available treatment to prevent ventricular arrhythmia in patients susceptible to hypokalaemia, such as those with heart failure. Potassium supplementation alone is not sufficient to alter mortality. QT prolongation and intracellular Ca2+ loading with subsequent diastolic Ca2+ release via ryanodine receptors (RyR2) are considered the predominant arrhythmogenic mechanisms in hypokalaemia-induced ventricular arrhythmia. We investigated the antiarrhythmic actions of two RyR2 inhibitors: dantrolene and VKII-86, a carvedilol analogue with no β-blocking activity, in hypokalaemia. Methods: Surface ECG and ventricular action potentials (APs) were recorded from whole-heart murine Langendorff preparations. Ventricular arrhythmia incidence was compared in hearts perfused with low [K+], and those pre-treated with dantrolene or VKII-86. Whole-cell patch clamping was used in murine and canine ventricular cardiomyocytes to study the effects of dantrolene and VK-II-86 on AP parameters in normal and low [K+] and the effects of VK-II-86 on the inward rectifier current (IK1), late sodium current (INa_L) and the L-type Ca2+ current (ICa). Effects of VKII-86 on IKr were investigated in HEK-293 cells transfected with KCNH2. Results: Dantrolene significantly reduced the incidence of ventricular arrhythmias induced by low [K+] in explanted murine hearts by 94%, whereas VKII-86 prevented all arrhythmias, p<0.001. VKII-86 prevented hypokalaemia-induced AP prolongation and depolarization of the resting membrane potential (p<0.001) but did not significantly alter AP parameters under normokalaemic conditions. Hypokalaemia was associated with a significant reduction of IK1 and IKr, and a significant increase in INa-L, and ICa. VK-II-86 prevented all hypokalaemia-induced changes in ion-channel activity (p<0.05 in each case). Conclusions and Implications: VKII-86 prevents hypokalaemia-induced arrhythmogenesis by normalising intracellular calcium homeostasis and repolarization reserve. The fact that VKII-86 does not have beta-blocking activity and does not alter AP parameters in normal [K+] is promising for future tolerability and electrophysiological drug safety testing, respectively. This unique pharmacological profile may provide an exciting treatment option in hypokalaemia and other arrhythmias caused by delayed repolarization or Ca2+ overload such as heart failure and the Long QT Syndromes. Conflict of Interest: None